Facilitators and barriers to the implementation of the picture exchange communication system (PECS): a systematic review - Paris, Andreas; Denne, Louise D.; Grindle, Corinna F.; May, Richard; Apanasionok, Magdalena M.; Hastings, Richard P. (Frontiers in Education, 2024)
Although there are several published systematic reviews and meta-analyses of the effectiveness of the Picture Exchange Communication System (PECS) protocol, no previous review has focused on factors affecting its implementation. The present review attempted to identify potential barriers and facilitators in implementing PECS, as well as examining authors' and stakeholders' views and experiences in terms of implementation.A total of 49 studies were identified through a systematic review search process and were included in the data extraction phase. A Content Analysis of previous researchers' comments was also carried out.During the data extraction and synthesis phase, it became evident that important features of PECS interventions are not systematically reported in published literature. Thus, our primary research question remained partially unanswered. A Content Analysis of previous researchers' comments revealed four potential implementation factors, including Contextual & Environmental Factors, PECS Training/Consultation, Supervision and Implementation Fidelity and Adherence to the Protocol.The identification of potential barriers or facilitators affecting the implementation of PECS is not currently possible. The present review's identified implementation factors were extracted from qualitative analysis of previous researchers' anecdotal remarks or from the social validity measures. Implications in terms of previous PECS literature findings are discussed.